Risk Aversion and Optimal Trade Restrictions - Young, Leslie; Anderson, James E. (Review of Economic Studies, 1982)
If the representative consumer of a country is risk averse then the choice of trade controls must take account of their effects on the fluctuations of domestic real income. If the world price of the importable is uncertain and risk aversion is high then the optimal policy for achieving a ceiling on expected imports involves a reduction in imports and a rise in the domestic price as the world price falls. Moreover, a quota is superior to a tariff in achieving the ceiling. Under domestic uncertainty, a tariff is superior to a quota but it could be optimal to reduce the domestic price as imports increase.